Itinerário educacional de uma aluna cega e a busca pela imagem adaptada - Oliveira, Rubem Varela de (2008)
The scope of this study directs an investigation in search of how the blind person learns knowledge at school mediated by the image in context of an inclusive education and how it can be (or is) triggered by the adaptation of images to the tactile seizure of the blind person and his correlative process of reading. To achieve this intent we choose a qualitative approach of research and opted for the modality of case study, based on the empirical field of a public school in the city of Cruzeta, RN and as a the main subject a congenitally blind female student enrolled in high school there, focusing, often, on the discipline of geography in its words mapping. Our procedures for construction of data are directly involved to the documentary analysis of open reflective interview and observation. The base guiding theory of our assessments is located in the current understanding about the human psychological development of its educational process inside an inclusive perspective, of contemporary conceptions about the visual disability as well of image as a cultural product. Accordingly, the human person is a concrete subject, whose development is deeply marked by the culture, historically built by human society. This subject regardless of his specific features, grasping the world in an interactive and immediate way, internalising and producing culture. In this thinking, we believe that the blind person perceives in multiple senses the stimuli of his environment and acts in the world toward his integration into the social environment. The image as a product of culture, historically and socially determined, appears as a sign conventionally used as an icon that in itself concentrates knowledge of which the student who does not realize visually himself and his surroundings cannot be excluded. In this direction, the inclusive educational process must build conditions of access to knowledge for all students without distinction, including access to the interpretation of the images originally intended for the seizure strictly visual to other perceptive models. Based in this theory and adopting principles of content analysis, we circulated inside the interpretation of the data constructed from the analysis of documents, from the subject speeches, from records of the observation made in the classroom and other notes of the field daily. In the search for pictures on the school contents, adapted to the tactile seizure of blind student, was seen little and not systematic in practice and teaching at the school. It showed us the itinerary of the student life marked by a succession of supports, most of the time inappropriate and pioneers in cooling the construction of her autonomy. It also showed us the tensions and contradictions of a school environment, supposedly inclusive, that stumbles in search of its intent, in the attitudinal and cumulative barriers brought, because of its aggravating maintenance. These findings arose of crossing data around of a categorization that gives importance to 1) Concepts regarding the school inclusion, 2) Elements of the school organization, educational proposal and teaching practice, 3) Meaning of the visual image as the object of knowledge, 4) Perception in multiple senses and 5) Development and learning of the blind person before impositions of the social environment. In light of these findings we infer that it must be guaranteed to the disabled person removal of the attitudinal barriers that are against his full development and the construction of his autonomy. In that sense, should be given opportunity to the student with visual disability, similarly to all students, not only access to school, but also the dynamics of a school life efficient, that means the seizure of knowledge in all its modalities, including the imagery. To that end, there is a need of the continued training of teachers, construction of a support network in response to all needs of students, and the opportunity to development of reading skills beyond a perspective eminently focused in the sight